Internet Governance: The visible and the invisible hand - Fredrik Lindeberg (International Telecommunications Society (ITS), 2017)
Who governs the Internet is a hotly debated subject, and there seems to be a lack of consensus. In this text I aim to show how central Internet functions are coordinated and which consequences that have on how we can consider the Internet to be governed. I show that the Internet has no governor, not even ICANN, and that there are several important actors for the development and function of the Internet, of which the ISPs stand out as the most influential since they can define what Internet access is for most Internet users in the short term. On a longer term there appears to be outside pressure in need of increased regulation which ICANN seems to respond to with amended bylaws and a more formalized multistakeholder model. ICANN, although not a governor with regulatory power, is shown to have governance consequences just by existing as the administrative home of the IANA function. Also fills an organizational void and prevents others from assuming the role of coordinating the Internet's unique identifiers. If viewed as an organization the Internet fits into the adhocratic form in the typology of Mintzberg (1993). The text is based on interviews, informal discussions and literature.
Keywords: 330